الضغط المدرسي وعلاقته بالدافعية للتعلم دراسة ميدانية على عينة من تلاميذ السنة الثانية ثانوي بثانوية بوجمعة قرمة غرداية (Revue El-Wahat pour les Recherches et les Etudes, 2021)
The Study Aimed At Uncovering The Relationship Between The Pressure Of School And The Motivation To Learn. The Study Was Shortened To A Sample Of Students From The Second Year Of Secondary School Boudjemaa Qarma, Ghardaia. The Study Sample Consisted Of 71 Students And Students Who Were Chosen In A Deliberate Intentional Manner. 19.0) Spss, Correlation Coefficient Pearson, The Equation Of The Difference Between The Correlation Coefficients Of The Sex Variable Where The Results Reached The Following:-There Is No Relationship Between The Pressure Of School And Motivation To Learn For Students In The Second Year Secondary High School In Boudjemaa Qarma. -The Level Of School Pressure Among Second-Year Secondary Students At The High School In Boudjemaa Qarma Is High.-The Level Of Motivation For Learning Among Second Year Secondary Students At The High School In Boudjemaa Qarma Is High.-The Relationship Between School Pressure And Motivation Among Second Year Secondary School Students Differs Sex In Boudjemaa Qarma. Keywords- School Pressure - Motivation To Learn - Second Secondary Students.